(untitled) (Environmental Smoke, 2023)
There are many challenges hinder the digital inclusion of people over 60. It is understood that the logic of inventions is to contribute to society. However, over the years, as technological evolution becomes necessary and develops rapidly, some generations, among them older people, need help keeping up with or adapting to them. Through exploratory research with a qualitative approach, where bibliographical research and the application of a questionnaire were used, we selected older adults of both sexes, in which we sought to analyze the appropriation and use of ICTs by older adults affiliated with the Cooperative Cresol União dos Pinhais, located in Coronel Vivida, a city in the mesoregion of Southwest Paraná, describing their main challenges facing digital inclusion. In general, the interviewees demonstrated the appropriation of ICTs, even with some difficulty and technical and skill challenges. However, they are aware of the importance of improving the use of the tools for their cognitive development and other potentialities related to decision-making in their rural property.